Bertrand Russell: from Neo-Idealism to Mathematical Logic - Genna, Caterina (Filosofia, 2023)
This essay is dedicated to the transition from neo-idealism to neo- positivism at Trinity College Cambridge at the beginning of 20th century. In 1903 George Edward Moore’s The Refutation of Idealism and Bertrand Russell’s The Principles of Mathematics marked the birth of mathematical logic. Especially Russell’s The Principles of Mathematics contain the theory of classes and the notion of denoting for the development of neo-positivism, then logical empiricism in the European continent. The objective of the article consists of underline the central position of neo-positivism in the twentieth-century philosophy. Indeed neo- positivism of Trinity College Cambridge has to be linked to the logical empiricism of the Vienna Circle, of the Berlin Circle and of the Lvov-Warsaw School. In that sense, the history of contemporary thought can be interpreted by the duality idealism/anti-idealism.